24.1: Invited Paper: Development of 55 inch 4K AMOLED TV by Inkjet Printing Process. (4th October 2019) - Wu, Zhongyuan; Shih, Huaiting; Wang, Huifeng; Liao, Jinlong; Ma, Kaihong; Yan, Liangchen; Yu, Jianwei
Abstract : This paper proposed a 55 inch 4K AMOLED TV by using Inkjet printing process. The backplane is based on bottom emission structure with Oxide TFTs, and color filter is integrated on array to achieve wide color gamut. The R/G/B pixels are designed with different aperture ratios to avoid white color shirt during the OLED device decay. The inkjet printing process is optimized by backplane pre‐treatment, nozzle stability maintaining and drying process tuning to implement mura‐free display. The prototype TV shows the good display quality with a high degree of uniformity and wide color gamut. It proves that the inkjet printing process is very promising to be used to manufacture the large‐size and low‐cost AMOLED displays.